The area of the room that is not covered by the rug is: [tex]21x^3+26x^2-24x+9[/tex]
Step-by-step explanation:
Let L be the length of the room
and
W be the width of the room
Then
L = 3x^2
W = 7x+14
Area of the bedroom:
[tex]A_r = L*W\\=3x^2(7x+14)\\=21x^3+42x^2[/tex]
Area of Rug:
Let S be the side of rug
S = 4x+3
[tex]A_{rug} =S^2\\=(4x+3)^2\\=(4x)^2+2(4x)(3)+(3)^2\\=16x^2+24x+9[/tex]
The area of the room that is not covered by the rug will be obtained by subtracting the area of the rug from the area of the room.
So,
[tex]Area\ of\ room\ not\ covered\ by\ rug =A_r - A_{rug}\\= 21x^3+42x^2-(16x^2+24x+9)\\=21x^3+42x^2-16x^2-24x-9\\=21x^3+26x^2-24x+9[/tex]
Hence,
The area of the room that is not covered by the rug is: [tex]21x^3+26x^2-24x+9[/tex]
Keywords: Rectangle, square
Learn more about area at:
brainly.com/question/10703930brainly.com/question/10772025#LearnwithBrainly
Which of these scatter plots has a trend line that would lie closest to y=x?
A. Scatter plot A
B. Scatter plot B
C. Scatter plot C
D. Scatter plot D
Correct Answer: A. Scatter plot A
Explanation: The line y=x slopes upward from the lower left corner of the graph to the upper right corner, at a 45-degree angle. The scatter plot whose points most closely match that trend is scatter plot A.
Answer:
A. Scatter plot A.Step-by-step explanation:
We need to find the scatter plot that is closest to y = x.
First of all, you must know the behaviour of y = x. That equation represents a straight line that passes through the origin of the coordinate system.
So, the right scatter plot must have the majority of points on this line that passes through the origin.
Notice that the Scatter plot A has this beahivour, if you draw a straight line through the origin and the points, you'll observe that the line best fits.
On the other hand, the other scatter plots are not following this linear behaviour.
Therefore, the right answer is A.
Divide ..............
The quotient is: 4a-5
The remainder is: 0
Step-by-step explanation:
We need to divide -40a^6+50a^5 by -10a^5
The division is shown in figure attached.
The quotient is: 4a-5
The remainder is: 0
Keywords: Division of polynomials
Learn more about Division of polynomials at:
brainly.com/question/11207748 brainly.com/question/1332667 brainly.com/question/1357167#learnwithBrainly
Which pair of triangles below shows the AAS Postulate. Explain
Answer:
We can conclude that Δ XYZ ≅ Δ RST by AAS postulate
Step-by-step explanation:
Δ XYZ and Δ RST are congruents by AAS postulate because:
1. Their non-included sides YZ and ST are equal (10 units = 10 units).
2. Their angles ∠Y and ∠S are equal.
3. Their angles ∠X and ∠R are equal.
4.Their non-included sides XZ and RT are equal.
Now, we can conclude that Δ XYZ ≅ Δ RST by AAS postulate.
You roll a 6-sided die.
What is P(prime)?
Write your answer as a percentage.
Submit
You roll a 6-sided die. The probability of getting prime is 50%.
Solution:
Given, that we have rolled a 6 – sided die.
We have to find the P(prime) as percentage.
Now, It means that we have to find the probability of getting a prime number on the face.
On rolling a six sided die, the total possible outcomes are 1, 2, 3, 4, 5, 6
Number of possible outcomes = 6
We have to get a prime number on rolling a die
The prime numbers in possible outcomes are 2, 3, 5
So number of favorable outcomes = 3
[tex]\text {Probability of an event as percentage }=\frac{\text { favourable number of outcomes }}{\text { total number of outcomes }} \times 100[/tex]
[tex]\text {Probability of getting prime number on face of die }=\frac{3}{6} \times 100[/tex]
[tex]\begin{array}{l}{\text { P(prime) }=\frac{1}{2} \times 100} \\\\ {\text { P(prime) }=50 \%}\end{array}[/tex]
Hence, probability of getting prime is 50%.
solve with the quadratic formula
4×^2×+1=0
Answer:
Either x = + i/2 or x = i/2 is the solution for the given quadratic equation.
Step-by-step explanation:
Here, the given quadratic equation is:[tex]4x^2 + 1 = 0[/tex]
Now, comparing the given equation with standard Quadratic Form, [tex]ax^2 + bx + c = 0[/tex]
we get,a = 4, b =0 and c = 1
Now, the Quadratic Formula is given as:
[tex]x = \frac{-b \pm \sqrt{b^2 - 4ac} }{2a}[/tex]
So, here the solution for the given expression is:
[tex]x = \frac{0 \pm \sqrt{(0)^2 - 4(4)(1)} }{2(4)} = x = \frac{0 \pm \sqrt{-16} }{8}\\\implies x = \frac{0 \pm4i}{8}\\\implies x = \frac{0 + 4i}{8} = \frac{i}{2} \\or, x = \frac{0 - 4i}{8} = \frac{-i}{2}[/tex]
Hence, either x = + i/2 or x = i/2 is the solution for the givenquadratic equation.
describe a situation that can be modeled by the integer -15 explain what zero represents in the situation
Answer:
Step-by-step explanation:
The current weather in a strange place is known to be 0 degrees, after a couple of hours, the weather has dropped 15 degrees, making the day much more colder than usual. What's the degree after the weather has dropped?
Solution:
0-15=-15
The integer -15 can be used to describe a situation of temperature falling below freezing point or owing someone money. In these situations, zero represents the freezing point or balanced position (no debt) respectively.
Explanation:A situation that can be modeled by the integer -15 could be the temperature outside on a very cold day in winter. If we are expressing the temperature in degrees Fahrenheit, for instance, a temperature of -15 could represent a day that is 15 degrees below the freezing point, which is 32 degrees Fahrenheit. In this situation, the integer zero represents the freezing point. So, if the temperature is -15, it means the temperature is 15 degrees below the freezing point.
Another example could be a debt. If you owe someone $15, then your balance can be represented by -15. In this case, zero represents the point where you do not owe any money, it is the neutrally balanced point of your financial situation.
Learn more about Integer Representation here:https://brainly.com/question/34482011
#SPJ11
If a person weighs 240 pounds on Earth, what would be the difference in weight of the same person on Mars and on the Moon (based on the table and graph)?
The person weighs 56 pounds more on Mars than on the Moon.
The person weighs 56 pounds more on the Moon than on Mars.
The person weighs 560 pounds more on Mars than on the Moon.
The person weighs 560 pounds more on the Moon than on Mars.
Answer:
The answer is A.
Step-by-step explanation:
Just took the test. You are welcome.
Use the following function rule to find f(4).
f(x) =
7
x
+ 5
HERE IS THE ANSWER 85
Answer:
33
Step-by-step explanation:
substitute 4 in the place of x.
multiply 4 by 7 then add 5 and your answer is 33.
Need help with number 1 and explain
Answer:
0
Step-by-step explanation:
If the answer is between 0 to 0.49, the best estimate is 0.
If the answer is between 0.5-1.49, the best estimate is 1.
If the answer is 1.5 or greater, the best estimate is 2.
Without giving the fractions 1/10 and 1/12 a common denominator, we know the answer is between 2/12 and 2/10.
2/12 is less than 2/10. 2/10 is 0.2, which is less than 0.5.
Since the final answer is less than 0.5, the best estimate is 0.
perform the indicated operation square root of 8 + square root of 50
Answer:
√8 + √50
= 2√2 + 5√2
=√2(2+5)
= 7√2
Hope this helps!
Evaluate the expression when m=6 and n= 7
8n+m
Answer:
62
Step-by-step explanation:
8 x n + m = ?
8 x 7 + 6
8 x 7 = 56
56 + 6 = 62
Answer: 62
Step-by-step explanation:
solution here m=6,n=7,and 8n+m=? now 8n+m =8×7+6 =56+6 =62
Tim is laying ceramic tile on a kitchen floor. Each tile costs $3.19. How much do 100 tiles cost?
-3,6,-9,12,-15 which of the following represents the general term for the sequence give?
(-1)^n3^n
(-1)^n3n
(-1)^n+1(3)
The general term for the sequence [tex]a_{n}=(-1)^{n} 3 n[/tex]
Solution:Given sequence is -3, 6, -9, 12, -15
We have to find the general term of sequence
The terms in the sequence are found out by using the recursive definition:
[tex]a_{n}=(-1)^{n} 3 n[/tex]
Let us use this definition to find out the terms and check if it matches our given sequence
[tex]\begin{array}{l}{\text { For } n=1:-(-1)^{n} 3 n=(-1)^{1} \times 3 \times 1=-3} \\\\ {\text { For } n=2:-(-1)^{n} 3 n=(-1)^{2} \times 3 \times 2=1 \times 6=6} \\\\ {\text { For } n=3:-(-1)^{n} 3 n=(-1)^{3} \times 3 \times 3=-1 \times 9=-9} \\\\ {\text { For } n=4:-(-1)^{n} 3 n=(-1)^{4} \times 3 \times 4=1 \times 12=12} \\\\ {\text { For } n=5:-(-1)^{n} 3 n=(-1)^{5} \times 3 \times 5=-1 \times 15=-15}\end{array}[/tex]
Thus the general term is given by [tex]a_{n}=(-1)^{n} 3 n[/tex]
Find the slope of (-6,2) and (-4,13)
We can use the points (-6, 2) and (-4, 13) to solve.
Slope formula: y2-y1/x2-x1
= 13-2/-4-(-6)
= 11/2
______
Best Regards,
Wolfyy :)
If f(x) = –4x^2 – 6x – 1 and g(x) = –x^2 – 5x + 3, find (f – g)(x)
Answer:
B
Step-by-step explanation:
Note (f - g)(x) = f(x) - g(x)
f(x) - g(x)
= - 4x² - 6x - 1 - (- x² - 5x + 3) ← distribute parenthesis by - 1
= - 4x² - 6x - 1 + x² + 5x - 3 ← collect like terms
= - 3x² - x - 4 → B
What is the genotype of the offspring missing on the first row of the Punnett square?
A. IBIB
B. IAIB
C. IBiO
D. none of the above
Answer:
Option B
Step-by-step explanation:
On the first row of the Punnett square, the offspring inherits IA from one parent and IB from another parent hence the resulting genotype is IAIB.
Which expression is equivalent to 3/4(4h-6)
Answer:
3h-9/2
Step-by-step explanation:
3/4(4h-6)=3h-18/4
simplify
3h-9/2
Answer:
3(3h-3/2) in its simplified form.
Step-by-step explanation:
Given the equation 3/4(4h-6),
First we will open the bracket up by multiplying through by 3/4 to have;
3h - 9/2
Since 3 is common at both sides of the resulting equation, we will factor it out to have;
3(h-3/2).
Since we cannot simplify further, then the expression 3/4(4h-6) is also equivalent to 3(h-3/2).
If gas prices increase 11% from $3.50 over the next month, what will the new price of gas be at the end of the month?
pls help :(
Multiply the current price by 1 + percentage of increase.
3.50 x 1.11 = 3.89
The new price will be $3.89
use two unit multipliers to convert 628 kilometers to centimeters
Using two unit multiplier 628 km is equal to 62800000 cm
Solution:
628 kilometer to centimeter
We will go from kilometers to meters to centimeters.
Start by putting 628 km over 1:
[tex]\frac{628 km}{1}[/tex]
We want to get rid of km and bring in m.
We know that 1000 m = 1 km.
Since km is in the numerator, we will make the first unit multiplier by putting 1 km in the denominator and 1000 m in the numerator, so the km will cancel. So we multiply by the unit multiplier,
[tex]\frac{628 km}{1} \times \frac{1000m}{1km}[/tex]
Now the km's will cancel:
[tex]\frac{628}{1} \times \frac{1000m}{1}[/tex]
Now we want to get rid of m and bring in cm.
We know that 100 cm = 1 m.
Since meter is in the numerator, we will make the first unit multiplier by putting 1 meter in the denominator and 100 cm in the numerator, so the meter's will cancel. So we multiply by the unit multiplier
[tex]\frac{100cm}{1m}[/tex]
[tex]\frac{628}{1} \times \frac{1000m}{1} \times \frac{100cm}{1m}[/tex]
We cancel the m's and we end up with:
[tex]628 \times 1000 \times 100 cm[/tex]
= 62800000 cm
Thus 628 km is equal to 62800000 cm
Final answer:
To convert 628 kilometers to centimeters, multiply by the conversion factors for kilometers to meters and then meters to centimeters, leading to 62,800,000 centimeters.
Explanation:
To convert 628 kilometers to centimeters, we need to apply two unit multipliers. The first conversion factor is 1 kilometer = 1000 meters, and the second conversion factor is 1 meter = 100 centimeters.
First, we convert kilometers to meters:
628 km × 1000 m/km = 628,000 meters
Then, we convert meters to centimeters:
628,000 m × 100 cm/m = 62,800,000 centimeters
Therefore, 628 kilometers is equal to 62,800,000 centimeters.
Could someone please answer question b) ii) ?
The question is on the attached image.
b) ii) The value of y when x is 2.5 is -1.5
How to find the value of y
b) ii) The value of y when x is 2.5 is read from the graph to be approximately -1.8
An mage is attached to show how to read the value.
This can be solved by substitution
For x = 2.5
y = (2.5)² - (2.5) - 3 = 1.75
find all the solutions in there interval (0,2pi) for cos5x=-1/2
Answer:
[tex]\frac{2\pi}{15},\frac{4\pi}{15},\frac{8\pi}{15},\frac{2\pi}{3},\frac{14\pi}{15}, \frac{16\pi}{15}, \frac{4\pi}{3},\frac{22\pi}{15}, \frac{26\pi}{15}, \frac{28\pi}{15}[/tex]
Step-by-step explanation:
Solving trigonometric equations.
We are given a condition and we must find all angles who meet it in the provided interval. Our equation is
[tex]cos5x=-\frac{1}{2}[/tex]
Solving for 5x:
[tex]5x=\frac{2\pi}{3}+2n\pi[/tex]
[tex]5x=\frac{4\pi}{3}+2n\pi[/tex]
The values for x will be
[tex]x=\frac{\frac{2\pi}{3}+2n\pi}{5}[/tex]
[tex]x=\frac{\frac{4\pi}{3}+2n\pi}{5}[/tex]
To find all the solutions, we'll give n values of 0, 1, 2,... until x stops belonging to the interval [tex](0,2\pi)[/tex]
For n=0
[tex]x=\frac{\frac{2\pi}{3}}{5}=\frac{2\pi}{15}[/tex]
[tex]x=\frac{\frac{4\pi}{3}}{5}=\frac{4\pi}{15}[/tex]
For n=1
[tex]x=\frac{\frac{2\pi}{3}+2\pi}{5}=\frac{8\pi}{15}[/tex]
[tex]x=\frac{\frac{4\pi}{3}+2\pi}{5}=\frac{2\pi}{3}[/tex]
For n=2
[tex]x=\frac{\frac{2\pi}{3}+4\pi}{5}=\frac{14\pi}{15}[/tex]
[tex]x=\frac{\frac{4\pi}{3}+4\pi}{5}=\frac{16\pi}{15}[/tex]
For n=3
[tex]x=\frac{\frac{2\pi}{3}+6\pi}{5}=\frac{4\pi}{3}[/tex]
[tex]x=\frac{\frac{4\pi}{3}+6\pi}{5}=\frac{22\pi}{15}[/tex]
For n=4
[tex]x=\frac{\frac{2\pi}{3}+8\pi}{5}=\frac{26\pi}{15}[/tex]
[tex]x=\frac{\frac{4\pi}{3}+8\pi}{5}=\frac{28\pi}{15}[/tex]
For n=5 we would find values such as
[tex]x=\frac{\frac{2\pi}{3}+10\pi}{5}=\frac{32\pi}{15}[/tex]
[tex]x=\frac{\frac{4\pi}{3}+10\pi}{5}=\frac{34\pi}{15}[/tex]
which don't lie in the interval [tex](0,2\pi)[/tex]
The whole set of results is
[tex]\frac{2\pi}{15},\frac{4\pi}{15},\frac{8\pi}{15},\frac{2\pi}{3},\frac{14\pi}{15}, \frac{16\pi}{15}, \frac{4\pi}{3},\frac{22\pi}{15}, \frac{26\pi}{15}, \frac{28\pi}{15}[/tex]
What do all simple machines have in common?
A
They have a mechanical advantage.
B
They have few or no moving parts.
C
They can be used to do work.
D
All of the above
Answer:
D: All of the above.
Step-by-step explanation:
A. All simple machines are useful in some way, weather that be making it easier to lift heavy objects, activating other machines, or something else.
B. Any simple machine must be, well, simple. i. e. have few moving parts.
Take the lever, for example. It has only one moving part, yet it is still very useful.
C. They can be used to do work. Simple machines can be put together to make something that can do work.
Imagine a windmill that generates power, which then is taken by a motor attached to an Archimedes screw. All of these machines are simple, yet they are still used to do work.
1. Refer to the equation 2x − 6y = 12.
(a) Create a table of values for at least 4 points. Show your work.
(b) Use the table of values to graph the line.
Answer:
In pictures.
Step-by-step explanation:
2x-6y=12
-6y=-2x+12
y=2/6x-2
Now the equation is in standard form.
Table in attachments.
Graph in attachments.
Sorry, I made a mistake somewhere and got 2 different lines.
This answer might not be right.
the williams have a farm that is in a rectangular shape. the length of the farm is hundred yards twice the width. the whole perimeter of the farm is 830 yards
Answer:
The length of the farm is 310 yards and the width is 105 yards
Step-by-step explanation:
The correct question is
The Williams have a farm that is in a rectangular shape. The length of the farm is one hundred yards more than twice the width. The whole perimeter of the farm is 830 yards
Find the dimensions of the farm
Let
x ----> the length of the rectangular farm
y ----> the width of the rectangular farm
we know that
The perimeter of the farm (rectangle) is equal to
[tex]P=2(x+y)[/tex]
we have
[tex]P=830/ yd[/tex]
so
[tex]830=2(x+y)[/tex]
simplify
[tex]415=(x+y)[/tex] -----> equation A
[tex]x=2y+100[/tex] ----> equation B
substitute equation B in equation A
[tex]415=(2y+100+y)[/tex]
solve for y
[tex]415=(3y+100)[/tex]
[tex]3y=415-100[/tex]
[tex]3y=315[/tex]
[tex]y=105\ yd[/tex]
Find the value of x
[tex]x=2y+100[/tex]
[tex]x=2(105)+100=310\ yd[/tex]
therefore
The length of the farm is 310 yards and the width is 105 yards
The diagonal of a square measured 7 square root of 2 cm. Find the length of a side of the square
The diagonal of a square measured 7 square root of 2 cm. Then the length of side of square is 7 cm
Solution:
Given that,
The length of diagonal of a square is [tex]7 \sqrt{2}[/tex] cm
The figure is attached below
So length of diagonal = AC = [tex]7 \sqrt{2}[/tex] cm
Let the length of sides of the square be ‘a’
Since, the diagonal and the sides are forming a right angled triangle
So, we can use Pythagoras theorem,
Pythagorean theorem, states that the square of the length of the hypotenuse is equal to the sum of squares of the lengths of other two sides of the right-angled triangle.
In triangle ABC, AC forms the hypotenuse and BC is the perpendicular and AB is the base
So above Pythagoras theorem definition,
[tex](\mathrm{BC})^{2}+(\mathrm{AB})^{2}=(\mathrm{AC})^{2}[/tex]
[tex]\begin{array}{l}{(a)^{2}+(a)^{2}=(7 \sqrt{2})^{2}} \\\\ {2 a^{2}=98} \\\\ {a^{2}=98 \div 2=49} \\\\ {a=\sqrt{49}=7}\end{array}[/tex]
Hence, the length of the square is 7 cm
Find the exact circumference of a circle with the given radius.
32 cm
C=
7.51 cm
71 cm
6.251 cm
The circumference of a circle whose radius is given would be =200.96cm.
How to calculate the circumference of a given circle?
To calculate the circumference of a given circle whose radius is given, the following steps should be taken as follows:
The formula for circumference = 2πr
where;
radius = 32cm
Circumference = 2× 3.14× 32
= 200.96cm.
The probability that an event will
occur is 0.25.
Answer:
PLEASE PROVIDE MORE INFORMATION
Step-by-step explanation:
What is the y-intercept of the line that is
parallel to the line 2x + 10y = 7 and contains
the point (4, 9)?
Answer:
Equation: 2x + 10y = 98
y-intercept: (0, 9.8)
Step-by-step explanation:
The easiest possible way to solve thios problem follows:
Keep the form of the given line 2x + 10y = 7, replacing the '7' with the constant 'c:'
2x + 10y = c
Now take the coordinates of the given point (4, 9) and substitute them into the above equation, to find c:
2(4) + 10(9) = c
Then 8 + 90 = c, and c = 98
Then the desired equation is 2x + 10y = 98
To find the y-intercept, let x = 0 and solve for y. We get
10y = 98, so that y = 9.8. The y-intercept is thus (0, 9.8).
The y-intercept of the line parallel to 2x + 10y = 7 and containing the point (4, 9) is 8.6.
Explanation:The y-intercept of a parallel line can be found using the equation y = mx + b, where m is the slope and b is the y-intercept. Since the given line 2x + 10y = 7 is in the form Ax + By = C, we need to rearrange it to the slope-intercept form. Therefore, the equation becomes: 10y = -2x + 7 → y = (-2/10)x + 7/10. The slope of the given line is -2/10, which means any line parallel to it will also have a slope of -2/10. Now we can use the point-slope form to find the equation of the parallel line that passes through the point (4, 9):
y - y1 = m(x - x1) → y - 9 = (-2/10)(x - 4)
Expanding and simplifying the equation, we get:
y - 9 = (-2/10)x + 8/10 → y = (-2/10)x + 8/10 + 9 → y = (-2/10)x + 86/10
Therefore, the equation of the parallel line that contains the point (4, 9) is y = (-2/10)x + 86/10. The y-intercept of this line is 86/10 or 8.6.
Learn more about parallel here:https://brainly.com/question/30097515
#SPJ2
please help quick will give brainliest
Answer:
.49
Step-by-step explanation:
So pretty much all you have to do is divide 8,526 by 42 which gives you .49, I know its pretty hard on paper but using a handy algebra calculator I was able to do it for ya :)
I need help with this homogeneous equation
[tex]\frac{dy}{dx} = \frac{x^{2}+y^{2} }{2xy}[/tex]
Answer:
[tex]ln [1 - (\frac{y}{x} )^{2} ] + ln x + c = 0[/tex]. This is the solution.
Step-by-step explanation:
The homogeneous differential equation is given by
[tex]\frac{dy}{dx} = \frac{x^{2} + y^{2} }{2xy}[/tex]
⇒ [tex]\frac{dy}{dx} = \frac{1 + (\frac{y}{x} )^{2} }{2(\frac{y}{x} )}[/tex] ........ (1)
Now to solve this differential equation we assume that y = vx where v is another variable.
So, differentiating with respect to x we get [tex]\frac{dy}{dx} = v + x \frac{dv}{dx}[/tex]
Therefore, the above equation (1) becomes
[tex]v + x \frac{dv}{dx} = \frac{1 + v^{2} }{2v}[/tex] {Since [tex]v = \frac{y}{x}[/tex]}
⇒ [tex]x\frac{dv}{dx} = \frac{1 + v^{2} - 2v^{2} }{2v}[/tex]
⇒ [tex]x\frac{dv}{dx} = \frac{1 - v^{2}}{2v}[/tex]
⇒ [tex]\frac{2v}{1 - v^{2} } dv = \frac{dx}{x}[/tex] {By separation of variables}
Now, integrating both sides we get,
[tex]\int {\frac{2v}{ 1- v^{2}}} \, dv = \int {\frac{dx}{x} } \, dx[/tex]
⇒ [tex]- \int {\frac{d(1 - v^{2} )}{1 - v^{2}}} = \int {\frac{dx}{x} }[/tex]
⇒ [tex]- ln (1 - v^{2}) = ln x + c[/tex] {Where c is the integration constant}
⇒ [tex]ln [1 - (\frac{y}{x} )^{2} ] + ln x + c = 0[/tex] (Answer)